2021
DOI: 10.1111/1462-2920.15655
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic insights into soil microbial communities involved in carbon cycling along an elevation climosequences

Abstract: Summary Diversity and community composition of soil microorganisms along the elevation climosequences have been widely studied, while the microbial metabolic potential, particularly in regard to carbon (C) cycling, remains unclear. Here, a metagenomic analysis of C related genes along five elevations ranging from 767 to 4190 m at Mount Kilimanjaro was analysed to evaluate the microbial organic C transformation capacities in various ecosystems. The highest gene abundances for decomposition of moderate mineraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 77 publications
(98 reference statements)
2
28
0
Order By: Relevance
“…recalcitrant carbon) but fewer simple resources (e.g. simple sugars) (Dai et al ., 2021), A‐strategists should outcompete other strategists by investing in extracellular enzyme machinery, and thus catalyse polymer decomposition, likely leading to declined microbial litter decomposition and soil carbon loss with increasing elevations. The complexity of microbial traits could also be quantitatively simplified by a newly developed framework into synthetic axes to define a low‐dimensional trait space and to cluster species based on their traits while identifying those species with unique combinations of traits (Mouillot et al ., 2021).…”
Section: Key Questions and Perspectivesmentioning
confidence: 99%
“…recalcitrant carbon) but fewer simple resources (e.g. simple sugars) (Dai et al ., 2021), A‐strategists should outcompete other strategists by investing in extracellular enzyme machinery, and thus catalyse polymer decomposition, likely leading to declined microbial litter decomposition and soil carbon loss with increasing elevations. The complexity of microbial traits could also be quantitatively simplified by a newly developed framework into synthetic axes to define a low‐dimensional trait space and to cluster species based on their traits while identifying those species with unique combinations of traits (Mouillot et al ., 2021).…”
Section: Key Questions and Perspectivesmentioning
confidence: 99%
“…In this study, SCC showed significant increases in the glyoxylate and dicarboxylate metabolism and twocomponent systems in water relative to SC. Glycoxylate and dicarboxylate metabolism are typical C metabolic pathways, and two-component systems are essential for C metabolism [45]. The above results indicated that S. constricta may mainly cause a shift C cycling in the water of shrimp-crab ponds.…”
Section: Discussionmentioning
confidence: 78%
“…Though alpha diversities (e. g. Shannon indexes) may be monotonically decreased with elevation increasing, the U-trend of beta diversity in our study was in accordance with previous studies ( Nottingham et al, 2018 ). These results suggested that though the dissimilarity of soil bacterial communities was affected by multiple environmental factors ( Dai et al, 2021 ), changeable conditions at low or high elevation area sustained higher biodiversity than that at long-term stability environment in middle elevation area ( Simpson, 1980 ). Moreover, if continuous samplings were obtained in karst graben basin of Yunnan-Kweichow Plateau, the real changing rules may be not U-trend.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that environmental conditions determine soil bacterial compositions ( Xun et al, 2015 ), and the occurrence and functioning of soil bacteria depend on their niches ( Banerjee et al, 2018 ), soil bacterial abundances (e.g., Acidobacteria, Actinobacteria, Proteobacteria, Verrucomicrobia, Firmicutes, Chloroflexi, Gemmatimonadetes, Bacteroidetes, Planctomycetes, Nitrospirae, and Latescibacteria) can follow hump-shaped, decreasing, increasing or U-shaped patterns along altitudinal gradients. These bacteria followed the above patterns due to them at their own optimum conditions though the responses of their ecological lifestyles to altitudinal gradients remain unclear ( Nottingham et al, 2018 ; Dai et al, 2021 ). Besides that, the different distribution patterns of bacteria taxa in two layers may be due to their response depending on soil depth ( Barbour et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%